MGNREGA for Inclusive growth: A Case Study of Manipur (International Journal of Food and Nutritional Sciences, 2022)
The study aims to evaluate the effectiveness of the MGNREGA (Mahatma Gandhi National Rural Employment Guarantee Act) in promoting inclusive growth in Manipur. By analysing data from both primary and secondary sources, the research focuses on two districts - Imphal West (valley) and Chandel (hill) - with a sample size of 391 MGNREGA beneficiaries. The findings suggest that MGNREGA positively impacts rural lives by generating employment, fostering social inclusion for marginalized groups, increasing beneficiary income, reducing poverty, enhancing women's economic independence, boosting local purchasing power, and creating long-term assets for individuals and communities.